Effect Of Calcitrol And Calcium Supplementation In The Prevention Of Glucocorticoid-Induced Osteoporosis Among Systemic Lupus Erythematosus Patiens - CHIN, CHAN LEE (2001)
Prolonged glucocorticoid therapy can lead to loss of bone mineral density (BMD) and higher risk of fracture. Fortunately this can be prevented or reduced if preventive measures are started early. Calcitriol (1 ,25-dihydroxyvitamin D3) and calcium supplementation is a rational therapy for minimising bone loss but has not been widely used locally. Our primary objective was to study the effect of calcitriol and calcium carbonate supplementation in the prevention of glucocorticoid-induced osteoporosis in our local systemic lupus erythematosus (SLE) patients. Our secondary objectives were to identify factors, which influenced the rate of bone loss in our SLE patients and also to see the effect of calcitriol and calcium carbonate on glucocorticoid-induced bone loss in the subgroup of patients with normal or reduced baseline BMD Sixty-nine SLE patients who were on long term glucocorticoid therapy were randomly assigned to receive either oral calcitriol 0.25 ).lg BD or calcium carbonate 1.25 gm BD for one year. BMD was measured every six months for a year by the same dual X-ray absorptiometry (DXA). There were no significant differences between groups at entry with respect to demographics and risk factors for osteoporosis. Analysis was done to see the effect of supplementation on the BMD of the spine and femur. Further sub-analysis was made to see the effect of supplementation on BMD of patients with normal bone density or osteopenia at entry. Calcitriol was more effective than calcium in preventing bone loss from the spine. Mean percentage change at 6 month for calcitriol and calcium were 2.16% and -0.55 % (p=0.05) respectively. While mean of change of BMD at one year for calcitriol and calcium were 0.52% and -0.32% respectively. Calcitriol also prevent bone loss from the femur in the first 6 months of the study (mean percentage change of 0.63o/o) but to a lesser degree than that in the spine. Calcium was unable to provide any protection against bone loss in the spine or femur. Those patients with osteopenic at baseline benefited most from calcitriol and calcium supplementation. When given calcitriol, their mean percentage increase in BMD of the spine were 3.62% at 6 month and 1.68% at one year. Those on calcium also showed an increase in BMD of 0. 77% and 1.66% respectively. Patients with normal baseline bone density showed an improvement only at the spine at 6 month (percentage increase of 1.12%) when given calcitriol supplementation. Calcitriol supplementation was more effective in preventing glucocorticoid-induced bone loss than calcium supplementation. Calcitriol with calcium supplementation offered protection against glucocorticoid-induced bone loss if given to patients who were osteopenia.